Penerapan Flipped Classroom untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pembelajaran Agama Katolik - Simbolon, Erikson; Sitepu, Elza Nadyia Br (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The critical thinking ability of students forms the foundation for developing competent learners. This critical thinking ability can be facilitated through the application of the Flipped Classroom learning model. The purpose of this research is to understand the implementation of the Flipped Classroom model to enhance students' critical thinking skills in Catholic religious education.Method – This research method used by researchers is qualitative. Data collection techniques were carried out through observation, interviews, and documentation. Data processing techniques are done through data reduction, data display, and conclusion drawing.Findings – The findings of this study indicate that improving students' critical thinking skills in Catholic religion learning can be done in two ways, namely the application of the Flipped Classroom learning model refers to discussion preparation and discussion activities as well as through interpretation, analysis, evaluation and inference. Research Implications – This research has relevant implications for the Flipped Classroom learning model on improving students' critical thinking skills. However, this research is limited by its focus on a conceptual approach without empirical testing so further research is needed to test the applicability of the learning model theory in actual practice in an educational setting.